The Natural History of Selborne, Vol. 1 - White, Gilbert, 1720-1793; Morley, Henry, 1822-1894 (Salt Lake City, UT : Project Gutenberg, 2007)
"The Natural History of Selborne, Vol. 1" by Gilbert White is a natural history book first published in 1789. Compiled from letters to fellow naturalists, phenological observations, and systematic notes on species, this work chronicles the wildlife and landscape around White's Hampshire village. The seemingly simple correspondence creates an intimate portrait of pre-industrial English countryside, pioneering ecological observation through careful documentation of seasonal patterns and animal behavior. Continuously in print with nearly 300 editions, it has charmed readers for over two centuries with its accessible approach to nature study. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Natural_History_and_Antiquities_of_Selborne
Release date is 2007-03-29
Les Bowler
Keywords: Natural history -- England -- Selborne -- Early works to 1800; Selborne (England) -- Description and travel -- Early works to 1800; Selborne (England) -- Antiquities -- Early works to 1800